Work-related asthma among workers in the Mozambique wood processing industry - Chamba, Paulino Samuel (Department of Public Health and Family Medicine, 2022)
Background: Workers in the wood processing industry are exposed to a heterogeneous mixture of inorganic and organic particles comprising wood fragments, viable and non-viable microorganisms, endotoxins, glucans and allergens, with the potential to cause work-related asthma. While this association has been reported in diverse settings, few studies have comprehensively studied host and environmental risk factors for work-related asthma phenotypes associated with wood dust. The aim of this study was to determine the prevalence and risk factors for work-related asthma among workers in the Mozambiquan wood processing industry. Methods: A cross-sectional study of wood workers was conducted in 21 factories located in three Mozambiquan provinces that processed various indigenous wood species. The environmental exposure assessment component comprised systematic walk-through inspections of all factories and the measurement of inhalable wood dust to determine particulate, (1-3)-β-D-glucan and endotoxin concentrations. A random sample of 30 workers were selected from similarly exposed groups (EGs) working in 9 representative factories for personal environmental sampling using PAS-6 sampling heads connected to Gillian GilAir pumps. A total of 124 of personal inhalable dust samples were collected for analysis. For the health outcome assessment, 450 subjects completed an ECRHS questionnaire adapted for occupational studies and underwent spirometry accompanied with bronchial reversibility and fractional exhaled nitric oxide (FeNO) testing conducted during the work shift. In addition, sera were obtained to determine the atopic status of workers using the Phadiatop test. Multivariate multiple lean and logistic regression was conducted adjusting for known confounders in saturated models using STATA 12 computer software. Results: The environmental exposure assessment demonstrated that the mean inhalable concentrations were 3.29 mg/m3 (GSD: 3.04) dust particulate, 98 endotoxin units (EU)/m3 (GSD: 5.05) and 123 ng/m3 (1-3)-β-D-Glucans (GSD: 5.05). These concentrations are higher compared to international exposure standards, generally ranging between 0.5-5 mg/m3 for dust particulate and 90 EU/m3 for endotoxins. A significant (p<0.05) modest correlation was observed between dust particulate and endotoxin (Pearson r = 0.48) and glucan (r = 0.40) concentrations. In the multivariate models, certain wood species were significantly associated with increased inhalable dust particulate levels - mahogany bean (Afzelia quanzensis Welw) (GM ratio=3.39) and African sandalwood (Spirostachys Africana Sonder) (GM ratio=3.19), as was factory building features (closed and semi-closed buildings, GM ratio=2.14). Additional determinants of elevated endotoxin exposures included African sandalwood (GM ratio=9.21) and working in closed buildings (GM ratio=2.10), while working in semi-closed buildings (GM ratio=2.14) was the main determinant of elevated glucan levels. Damp cloth cleaning methods were associated with lower dust particulate (GM ratio=0.55), endotoxin (GM ratio=0.32) and glucan (GM ratio=0.53) levels. The health outcome assessment of study subjects found the mean age to be 38 years, mostly male (94%), a large proportion non-smokers (76%) and 50% were atopic. The prevalence of current asthma was 7%, with equal proportions of atopic and non-atopic asthma (4%), while 2% had work-related asthma. The main host factors associated with work-related asthma outcomes were age, gender and atopic status. Exposure to Missanda (Erythrophleum suaveolens Brenan), Panga-panga (Millettia Stuhlmannii Taub.) and Mahogany bean (Afzelia quanzensis Welw.) wood species was associated with work-related ocular-nasal symptoms, while Mutondo (Cordyla Africana) species was associated with both work-related ocular-nasal and asthma symptoms. Work-related ocular-nasal symptoms were also associated, in a dose-dependent manner, with EGs categorized according to job titles as well as current dust particulate levels (medium, 4.68-4.71 mg/m3: OR = 3.45, 95% CI: 1.21 – 10.63; high, >4.71 mg/m3: OR = 3.66, 95% CI: 1.19 – 11.26) when compared to the low EG (<4.68 mg/m3) in unadjusted models. A similar trend was observed in the multivariate models adjusted for age, gender and smoking status. A history of work-related asthma symptoms was also positively associated with mean cumulative dust particulate exposure calculated across all jobs in the factory (OR = 1.01, 95% CI: 1.00 – 1.02) in multivariate linear regression models. In both unadjusted and adjusted models, increasing degree of bronchial reversibility was associated with increasing current dust particulate levels (medium, 4.68-4.71 mg/m3: OR = 1.99, 95% CI: 1.25 – 3.22; high, >4.71 mg/m3: OR = 1.73, 95% CI: 1.07 – 2.80) when compared to the low EG (<4.68 mg/m3). Increasing FeNO was associated with cumulative dust exposure quartiles based on current job >10.09 mg/m3-yr in both unadjusted (Q2, OR = 1.23, 95% CI: 1.02 – 1.51; Q3, OR: = 1.11, 95% CI: 0.91 – 1.35, Q4, OR= 1.23, 95% CI: 1.02 – 1.49) and adjusted models. Conclusion: This study demonstrated that exposure to all wood dust components in Mozambiquan wood processing workers were above international standards. The 7% asthma prevalence is consistent with global and specifically African country estimates, while 2% had work-related asthma. Processing of particular indigenous wood species and exposure metrics based on current as well as cumulative inhalable wood dust exposures were associated with an increased risk of work-related ocular-nasal and asthma symptoms, bronchial reversibility and airway inflammation. These risks are modified by host-associated factors of age, gender and atopy.